2021
DOI: 10.5430/rwe.v12n1p340
|View full text |Cite
|
Sign up to set email alerts
|

Firm Size and Financial Performance Among Listed Banks of Emerging Economies in Africa

Abstract: The continuous increase in the size of various firms and listed banks, has necessitated the need to empirically examine the effect firm size has on the financial performance of listed banks in Africa. This is because some organisations and institutions have in time past failed to fulfill their going concern objective despite their large firm size balance. This study examined the effect firm size has on the three levels of cash flow of emerging economies in listed banks in Africa. The study employed the use of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…The study found that all the independent variables (Firm Age, Firm Size, Sales Growth, Liquidity, and Leverage) jointly and strongly affected the financial performance of manufacturing firms in Nigeria, as measured by return on assets. Umukoro et al (2021) examined the effect of firm size on the three levels of cash flow in listed banks in African emerging economies using multiple regression analysis with the STATA statistical software tool. The results revealed that for the operating level of cash flow, all countries used in the study, except Kenya, should continue to employ firm size as a corporate strategy method, as it increases operating cash inflow.…”
Section: Empirical Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The study found that all the independent variables (Firm Age, Firm Size, Sales Growth, Liquidity, and Leverage) jointly and strongly affected the financial performance of manufacturing firms in Nigeria, as measured by return on assets. Umukoro et al (2021) examined the effect of firm size on the three levels of cash flow in listed banks in African emerging economies using multiple regression analysis with the STATA statistical software tool. The results revealed that for the operating level of cash flow, all countries used in the study, except Kenya, should continue to employ firm size as a corporate strategy method, as it increases operating cash inflow.…”
Section: Empirical Reviewmentioning
confidence: 99%
“…The few studies that were done were in industries other than consumer goods. The only study that particularly focused on firm size was Umukoro et al (2021). The researchers examined the relationship between firm size and the performance of banks in Nigeria.…”
Section: Gaps In Empirical Reviewmentioning
confidence: 99%